Suatu Inovasi Teknologi untuk Konservasi Pengembangan Timah Alluvial : Penambangan Hidrolis Bawah permukaan dengan Peralatan BTM-SR-4 - Ichwan Azwardi Lubis; Robertus Bambang Susilo; Sasri Romo (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2014)
Nowadays, surface hydrolic mining on tin alluvial has caused conflict with other interests. Due to a big mining area needed, the activity has conflict with plantation and local people gardens. Furthermore, activity of illegal mining has destroyed tin reserve and environment as well. Once the illegal mining is not managed properly, tin reserve of the company will decrease significantly, in addition, reclamation cost that must be beared by the company will increase significantly. Approach to manage conflict through negotiation on land use has not given a signifi-cant outcome. As the result, the company experiences a very difficult situation to make a mine planning, both short term and long term. Technology of subsurface hydrolic mining offers a mine activity with minimal land clearing and avoid to open overburden. Currently, PT Timah (Persero) Tbk has succeeded to study and examine the technology through operating a pack of equipment named BTM-SR4. Besides aware-ness on environment, due to its ability to mine on spotted tin deposit, the technology is able to increase tin reserve. Other good news are to decrease mining cost due to not opening over burden and to decrease reclamation cost. All of above good points will support sustainability of the company.